Political Interference and Tertiary Institutions in Nigeria - Ogunode, Niyi Jacob; Edinoh, Kingsley; Agbade, Olofu Paul (Indonesian Journal of Social Development, 2024)
This paper discussed the implication of political interference on tertiary institutions in Nigeria. Secondary data was used in the paper. The data were collected from print and online publications. The paper revealed the implication of political interference on tertiary institutions such as; recruitment of unqualified personnel, admission of less qualified candidate, internal administration, underdevelopment of tertiary institution, poor quality of tertiary education, poor governance and ineffective leadership, proliferation of tertiary institutions and alteration of planning and location of tertiary institutions across the country. Based on these discoveries, the paper suggested that the federal and state government should grant full autonomy to all tertiary institutions to allow the institutions operate independently.